Avaliação antitumoral de chalconas sintéticas em sistema nanoestruturado - Sampaio, Guilherme José Schwarzt (2024)
The difficulty faced in treating cancer has led to several researches aimed at developing systems that perform targeted drug delivery, with the aim of increasing the effectiveness of treatment and reducing adverse effects. In the present study, a series of substituted chalcones were evaluated for their cytotoxic action on gastric adenocarcinoma cells (AGS) and breast cancer cells (MCF-7) using the MTT tetrazolium method, highlighting 3-methoxychalcone, 3-chlorochalcone and 3 hydroxychalcone. Considering the physicochemical characteristics of these compounds, 3-hydroxychalcone was chosen for incorporation into mesoporous silica nanoparticles due to the presence of the hydroxyl group, which could favor the incorporation process through hydrogen interactions. The synthesis of mesoporous silica nanoparticles (MSN) and their surface modification with 3 aminopropyltriethoxylane (APTES) were carried out and, subsequently, 3 hydroxychalcone was incorporated into these materials. The mesoporous silica nanoparticles were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), elemental analysis (CHN), scanning electron microscopy (SEM), transmission electron microscopy (TEM), zeta potential and nitrogen adsorption. Furthermore, in vitro release tests were carried out to verify the release profile of 3-hydroxychalcone from mesoporous silica samples. The results obtained demonstrated that the mesoporous silica nanoparticles exhibited a gradual and prolonged release profile. In the cytotoxicity test with silica samples incorporated with 3-hydroxychalcone, important cytotoxic activity was observed (IC50 = 12.93 to 106.67 μM) against AGS and MCF-7 cells, with the MSN-CHO sample (IC50 = 12.93 to 22.30 μM) exhibited a cytotoxic effect superior to free 3-hydroxychalcone (IC50 = 47.58 to 47.97 μM). The results indicate that the nanoparticles positively influence the interaction of chalcone with tumor cells. Despite numerous published studies reporting the pharmacological potential of chalcones, few studies report the application of these compounds in drug delivery systems and the results obtained in this work indicate the great potential that these materials have for application in cancer treatment.